Mutations in the Foodstuff Quality Perception of the New Consumers in Romania - Dorin Popescu; Mihai Negrea; Lelia Voinea (Amfiteatru Economic Journal, 2011)
In the current context of the market, very complex and dynamic, we can observe the crystallization of a new generation of consumers, with a specific behavior and a particular manner of approaching the quality unlike the one of traditional consumer. The concept of quality, perceived by the traditional consumer in the classical, deterministic and objective sense, loses its facets nowadays and transcends into another dimension, in the vision of the new consumer, in which the perception of quality in a predominantly subjective manner, comes first. This paper presents the objectives of a research project that we intend to develop, in order to highlight the mutations that occurred in the foodstuff quality perception of the new consumers from Romania. We focused on foodstuff because it is a customary part of our daily lives, that shouldn't be approached merely as a common factor for meeting physiological needs of macro and micro-nutrients, but from a holistic perspective in terms of its social and identity functions and the effects on individual health. Another important goal of the project is to improve the standard of education and culture in foodstuff consumption and to give to the new consumers from Romania the skills for an objective assessment of food quality. We believe that all these could lead to the conversion of the new consumers of foodstuff in ethical and responsible consumers.
Keywords: P46; 330; new consumer; quality perception; mutations; foodstuff; ethical consumerism